Comparison of Methylprednisolone and Placebo toward Incidence and Severity of Epiretinal Membrane Post Pars Plana Vitrectomy in Rhegmatogenous Retinal Detachment - Salmarezka Dewiputri; Elvioza Elvioza; Aria Kekalih (International Journal of Retina, 2021)
Introduction: Epiretinal membrane is one post-operative complication of vitrectomy that can lead to decrease visual acuity. Epiretinal membrane is the early step of proliferative vitreoretinopathy caused by inflammation. Steroid has been used in the treatment of intraocular inflammation. The aim of this study is to compare oral methylprednisolone and placebo toward incidence and severity of epiretinal membrane post pars plana vitrectomy in rhegmatogenous retinal detachment. Methods: This was prospective, double blind, randomized clinical trial. Fourty six eyes who met inclusion criteria were randomized into 2 groups: 26 patients received oral methylprednisolone 0.8 mg /kgBW/day for 6 days, 0.4 mg/kg BW/day for 4 days, and 0.2 mg/kg BW/days for 4 days. The control group of 26 patients received placebo in a comparable manner. Result: Four weeks after vitrectomy incidences of epiretinal membrane were 47.6 % and 58.8 % in methylprednisolone group and placebo group, respectively. Eight weeks post vitrectomy incidences of epiretinal membrane was 47.6 % and 56.2 % in methylprednisolone group and placebo group, respectively. At 4 weeks the severity of epiretinal membrane in methylprednisolone group was 60%; 0%; 40% in grade 0, 1, and 2, respectively. Meanwhile, in placebo group were 60%; 10%; 30% in grade 0, 1, and 2,respectively. Eight weeks post vitrectomy the severity of epiretinal membrane in methylprednisolone group were 40%; 0 %; 60% in grade 0, 1, and 2, respectively. Meanwhile, at placebo group were 55.6 %; 11.1 %; and 33.3 % in grade 0, 1, and 2, respectively. Conclusion: There were no significant differences in incidence and severity of epiretinal membrane at 4 and 8 weeks among 2 groups. Oral methylprednisolone had a tendency to lower incidence of epiretinal membrane compared to placebo.